Unregulated serving sizes on the Canadian nutrition facts table - an invitation for manufacturer manipulations - Jessica Yin Man Chan; Mary J. Scourboutakos; Mary R. L'Abbé (BMC, 2017)
Abstract Background Serving sizes on the Nutrition Facts table (NFt) on Canadian packaged foods have traditionally been unregulated and non-standardized. The federal government recently passed legislation to regulate the serving sizes listed on the NFt. The objective of this study was to compare the serving sizes on food product NFts to the recommendations in the 2003 Nutrition Labelling regulation (Schedule M) reference amounts, the Canadian Food Inspection Agency (CFIA) ranges, and Canada's Food Guide recommendations. An additional objective was to determine if food and beverage products that report smaller serving sizes have a higher calorie density, compared to similar products with a larger serving size. Methods Data for 10,487 products were retrieved from the 2010 Food Label Information Program (FLIP) database and categorized according to Schedule M categories. Correlations between calorie density and manufacturer stated serving size were tested and the proportion of products meeting recommendations were tabulated. Results 35% of products had serving sizes on the NFt that were smaller than the Schedule M reference amount and 23% exceeded the reference amount. 86% of products fell within the CFIA's recommended serving size ranges; however, 70% were within the lower-half of the range. Several bread and juice categories exceeded CFG's recommendations, while several dairy product categories were smaller than the recommendations. Of the 50 Schedule M sub-categories analyzed, 31 (62%) exhibited a negative correlation between serving size and calorie density. Conclusion While most products fell within the CFIA's recommended serving size ranges, there was a tendency for products with a higher calorie density to list smaller serving sizes.